Multilayer Shielding Design and Analysis of Optimal Thickness for the Storage of Highly Radioactive Sources Concerning Environmental Safety - Md. Mahfuzul Haque Rafi; Asma Ul Husna; Abdus Sattar Mollah (International Journal of Nuclear Security, 2024)
As a kind of radiological protection, multilayer shielding is superior to a single-layer shield in terms of blocking off radiation. This study examined a multilayer shielding strategy to protect employees from potentially harmful gamma radiation from highly radioactive sources such as 60Co. This paper presents a novel strategy for cost-effective and environmentally safe radiation protection by aligning expensive and heavy materials such as W and Pb to improve their effectiveness and limit exposure below the occupational dose. The largely unpublished set of final exposure rates for the W–Pb–Fe combination was calculated by the numerical interpolation method in MATLAB software. Attention has been given to frequently neglected processes such as mean free path, source strength, and weight-to-cost ratio. The total optimal thicknesses and costs were found to be 33 cm at $5478.65 (USD), and 38 cm at $5831.14 for 60Co energies at 1.17 MeV and 1.33 MeV, respectively. The thickness was found in a successive manner that was verified with the theoretical data group. This method, procedure, and calculation are planned to be used for the storage of new or used fuel in a nuclear power plant.
Keywords: Multilayer radiation shielding; mass attenuation coefficient; linear attenuation coefficient; exposure rate; cost-effective ratio; buildup factor